AB0818 Which Patients with Psoriatic Arthritis Present Themselves to the Rehumatologist: Baseline Data from the Depar. (9th June 2015) - Vis, M.; Tchetverikov, I.; Kok, M.; Gerards, A.; Appels, C.; Groenendaal, H.V.; Krugten, M.V.; Korswagen, L.; Graaff, W.V.D.; Sonnaville, P.D.; Harbers, J.; Luime, J.
Abstract : Background: Psoriatic arthritis (PsA) is the second most common chronic arthritis. The CASPAR criteria are used to classify patients as having PsA for scientific research. 1 Currently there are no diagnostic criteria for PsA. The Dutch South-West Psoriatic Arthritis Registry (DEPAR) includes patients newly diagnosed with PsA. The diagnosis is made at the discretion of the rheumatologist. In this abstract we will report the characteristics of new PsA patients in daily practice. Objectives: To investigate the characteristic of patients newly diagnosed with PsA in daily clinical practice. Methods: The Dutch South-West Psoriatic Arthritis Registry (DEPAR) is prospective cohort study for newly diagnosed patients with PsA. The DEPAR is hosted by CICERO a collaboration of 11 hospitals including one academic hospital in the South West Part of the Netherlands. Patients with newly diagnosed PsA are included and followed for 2 years at regular intervals (0, 3, 6, 9, 12, 18 and 24 months). The diagnosis of PsA is made at the discretion of the treating rheumatologist. At baseline data is recorded on demographics, comorbidity, medication use, medical history, family history, work, quality of life and Disease activity. Results: The aim is to include 500 patients; this abstract describes the characteristics of the currently included 149 patients. (table 1 ) Fifty percent of patients are male with a mean (SD) age of 50, 1 (12, 8) years and have a median of 3 swollen joints (1-20) at presentation. The percentage of patients with polyarticular, oligoarticular and monoarticular disease was 35, 40 and 25 percent respectively. Conclusions: In our cohort most patients presented with a mild disease activity as measured by swollen and tender joint count, low PASI score and subsequently a low CPDAI score with only 3.2 percent in the severe range. In our region, a long standing practice of use of early arthritis clinics may have contributed to early referral of the patients and as a consequence, low disease activity state at the time of presentation. It may also be due to the fact that in daily practice, physicians tend to diagnose more patients with PsA than when using the CASPAR classification criteria. Also a majority of patients presented with oligo-/mono articular disease instead of polyarticular disease, which is studied most frequent in clinical trials. The use of DMARDs in our group of patients even with oligoarticulair disease shows the adaptation of early aggressive treatment strategies as used in rheumatoid arthritis and as such underlines the need of studies to estimate the effectiveness of such approach in daily practice. References: Taylor W, Gladman D, Helliwell P, et al. Classification criteria for psoriatic arthritis: development of new criteria from a large international study. Arthritis Rheum 2006;54:2665–73. Disclosure of Interest: None declared